The Relationship between Parental Behavior and Nutritional Status of Toddlers in Kawango Hari Primary Health Center - Hemba, Dominggus Dinga; Aspatria, Utma; Toy, Sarci Magdalena (Timorese Journal of Public Health, 2023)
Nutritional status is the state of the body caused by the balance between nutritional intake and needs. Toddlers who were malnourished in Southwest Sumba Regency in 2019 there were 348 cases. Kawango Hari Health Center there were 56 cases of malnutrition in 2019 and ranks the first highest cases of undernutrition than 16 health centers in Southwest Sumba district. The purpose of this study is to find out the relationship of parental behavior with the nutritional status of toddlers in the working area of ​​Kawango Hari Puskesmas Hari District Kodi Southwest Sumba Regency in 2021. This type of research is a survey study with a cross sectional study design. This research was conducted in March to April 2021 in the working area of ​​Kawango Health Center on Kodi District Of Southwest Sumba Regency. The population in this study was households that had toddlers in the working area of ​​Kawango Hari Health Center. The sample of 93 households was taken using the Cluster Random Sampling technique. The data was analyzed using the Chi-square test with a meaningful rate of =0.05.Results:research shows that there is a relationship between research variables and toddler nutritional status, namely maternal nutritional behavior (p = 0.002), maternal nutrition knowledge (p = 0.001) and maternal nutritional attitudes (p = 0.003). Conclusion: there is a relationship between parental behavior and nutritional status of toddlers in the work area of ​​Kawango Hari Health Center. It is recommended to parents, especially mothers, to know more about the nutritional needs of toddlers so as to improve the nutritional status of toddlers.